2009
DOI: 10.1063/1.3141062
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous yield reduction in direct-drive deuterium/tritium implosions due to H3e addition

Abstract: Glass capsules were imploded in direct drive on the OMEGA laser [Boehly et al., Opt. Commun. 133, 495 (1997)] to look for anomalous degradation in deuterium/tritium (DT) yield and changes in reaction history with H3e addition. Such anomalies have previously been reported for D/H3e plasmas but had not yet been investigated for DT/H3e. Anomalies such as these provide fertile ground for furthering our physics understanding of inertial confinement fusion implosions and capsule performance. Anomalous degradation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
24
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…Multiple ion species are not treated separately: the ion mass and charge are set as a weighted average of the individual species. Recent experimental and theoretical work has questioned the validity of the average-ion assumption [5][6][7][8][9][10][11][12][13][14][15]. Anomalous reduction of the compression-phase nuclear yield has been observed in implosions filled with multiple fuel species, such as deuteriumhelium-3 (D 3 He) [5], DT [6], and other combinations [7,8].…”
mentioning
confidence: 99%
“…Multiple ion species are not treated separately: the ion mass and charge are set as a weighted average of the individual species. Recent experimental and theoretical work has questioned the validity of the average-ion assumption [5][6][7][8][9][10][11][12][13][14][15]. Anomalous reduction of the compression-phase nuclear yield has been observed in implosions filled with multiple fuel species, such as deuteriumhelium-3 (D 3 He) [5], DT [6], and other combinations [7,8].…”
mentioning
confidence: 99%
“…For example, in an effort to explain observed yield anomalies in multiple-ion fuels of D 3 He, DT, and DT 3 He [7][8][9], researchers have investigated multiple-ionfluid effects [10][11][12] as well as utilized a hybrid fluidkinetic model [13,14]. Other modeling work has included ion viscosity and nonlocal ion transport [15] in order to reduce discrepancies with shock-generated nuclear yields.…”
mentioning
confidence: 99%
“…[4] that the d 3 he proton and dd neutron yields were about 50% lower than the expected in equimolar D 3 He gasfilled capsule implosions. In another study, non-hydroequivalent DT 3 He gas-filled capsule implosions have shown anomalous D(t,n) 4 He (dt) reaction yield behavior that was ~50% lower than expected [6]. A third study showed indirect-drive experiments, with trace Ar dopants in D 2 capsule implosions, which also had observed dd yields that were 30-50% of expectation [7,8].…”
mentioning
confidence: 96%
“…Generalizing these observations from the different elemental mixtures (different Z) of Refs. [4,6,7] to include isotopic mixtures of the same Z (e.g, Z=1 for hydrogen, deuterium, tritium), is of fundamental interest. The latter case is particularly important, as it is directly relevant to current ignition experiments at the National Ignition Facility (NIF), where different mixtures of H, D and T are being utilized.…”
mentioning
confidence: 99%